ANALISIS FAKTOR PENDORONG PROSES INTERAKSI SOSIAL PADA PESERTA DIDIK KELAS XI IPS DI MAN 2 PONTIANAK - Novi Ratna Ramadanti; Sulistyarini Sulistyarini; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of the research is "Analysis of the Supporting Factors of the Process of Social Interaction in Class XI IPS Students in MAN 2 Pontianak". The research method used is descriptive method, with the form of qualitative research. Sources of research data were students of class XI IPS 1 and XI IPS 2. The analysis in this study was presented in a descriptive qualitative manner, using eight informants. The results of his research are (1) the imitation factor encourages the social interaction process in class XI IPS students in MAN 2 Pontianak, namely at 06.30 WIB the students clean the class so that its beauty is maintained and carry out the morning routine by reading al-quran. (2) The suggestion factor encourages the social interaction process of class XI IPS students at MAN 2 Pontianak, namely the group work process goes well, when the time for prayer arrives students rush to carry out prayer services. (3) The empathy factor encourages the social interaction process in class XI IPS students at MAN 2 Pontianak, namely the feeling of worrying students towards their friends, collecting money for their families affected by the disaster aims to help other people's distress.Keyword: Factors Driving, Process of Social Interaction, Students.